Hairy Mountain Buttercup plants growing at the Tromsø Arctic-Alpine Botanical Garden - Campbell, Sandy (2024)
These Ranunculus insignis plants were blooming in the New Zealand section of the Tromsø Arctic-Alpine Botanical Garden (69° 38' 56.04" N) in early June.